RISE–The Pillars of Quality Assessment (Review, Identify, Strengthen, Evaluate) - Radhika Devi, V.; Bhaskara Reddy, P. (Journal of Engineering Education Transformations, 2017)
In recent times, Class-room Assessment Techniques (CATs) have gained momentum in the engineering education. Class-room Assessment Techniques are intended to evaluate the depth of knowledge gained by a student in a particular subject. Class-room Assessment Techniques are understandably useful in development/improvement of curriculum, as these are critical to determine the effectiveness of programs. When first designing a curriculum, it is important to begin by designing the rubrics for assessment. The RISE (Review, Identify, Strengthen, Evaluate)will help to identify the primary goal of the assessment and how can they be modified to improve the quality of engineering education. A well carried out assessment will provide an observable outcome. Without conducting an area specific assessment, it is impossible to know with any certainty what factors are most responsible for not attaining the desired outcome. Therefore, it is likely that assessments created without specific rubrics may not target the appropriate problem factors and will fail. Following from this, it is important that in order for any program to be effective, a proper assessment technique should be designed before the program is rolled out. This paper summarizes the findings of a project investigating the impact of assessment methods on the quality of engineering education. The key findings elaborated in this paper, concern the impact of existing methods of assessment and trends in the outcomes observed.